Examining Psychometric Properties of The Turkish Version of Job Satisfaction Scale for Clinical Nurses - Özlem Çağan; Bennur Koca (Dokuz Eylul University, 2020)
Background: Job satisfaction, which is one of the most important requirements of the people to be successful, happy and productive, is the feeling of contentment created by the perception of the job provided to the individual. Objectives: This study was performed to examine Psychometric Properties of The Turkish Version of Job Satisfaction Scale for Clinical (JSS-CN). Methods: Type of research is methodologically and the study included 300 nurses volunteering to participate in the study in two Research and Application Hospital. In adapting the scale into Turkish, the translation and back translation method was used. The Content Validity Index was used to test the content validity, the Confirmatory Factor Analysis was used for determine the construct validity, and Cronbach's alpha value and item total correlation were used to test the reliability. Results: The content validity index for JSS-CN was 0.99. The Cronbach alpha coefficient was 0.94. Scale consists of six subscales. These are institutional acceptance and professional success; the contribution of the profession to individual maturation; respect and acceptance in interpersonal relationships; awareness of professional responsibility; the appearance of professional competence and value of the profession. The alpha values of the six subscales were .85, .88, .80, .90, .80 and .80 respectively. Total score correlation coefficient of item range from .37 to .73. The fit indices were determined as RMSEA .086, GFI .76, CFI .96, IFI .96, RFI .93 and NFI .94. As a result of confirmatory factor analysis, a six-factor scale was verified. Conclusion: The JSS-CN scale is a reliable and valid measurement tool for determining the job satisfaction of nurses.